European Strategies for SME Competitiveness - Andreea Valeria FARCAȘ (Communications of International Proceedings, 2021)
SMEs play an important role in the economic development of the Member States and their growth is influenced by the European support strategies and initiatives for increasing competitiveness. The objective is analysing strategic EU-level documents on SMEs with the purpose of identifying how the SME support measures has evolved and what are the development directions.
Keywords: Small and medium-sized enterprises (SME); European strategies; SME initiatives.